Análisis de sistentabilidad de las fincas de los productores agropecuarios de la Parroquia La Esperanza Cantón Pujilí, Provincia de Cotopaxi - Morocho Valencia, Edwin Fernando (2017)
The farms viability of the watershed of the Pilalo River was analyzed, at coordinates X 0715668, Y 9894709 to the coordinate X 0715300, and 9894833 at a height of 2227 mnsm, up to altitudes of 684 msnm, being a pioneering research project due to analyzing production systems and living conditions of producers in the area. The primary objective was to analyze the sustainability of the farms. To carry out this research, the indicators were developed in the social, economic and environmental dimensions by the Santiago Sarandón´ methodology; once the information was classified and systematized by transects, the sustainability analysis was performed using the method, where the following results were obtained: G (General Index) = (S + E + A) / D with 2.3, which indicates that there is sustainability in the sector in general terms that was obtained from the average of the dimension with an average of 2.7 in the economic dimension was achieved with an average of 2.5 to see the environmental dimension obtained an average of 1.8, which notes that work must be done in this aspect.